Cell design for the electrodeposition of polyacrylonitrile onto graphite composite electrodes for use in lithium-ion cells. (May 2021) - Allen, Jonathan; Hector, Andrew; Garcia-Araez, Nuria
Abstract: Polyacrylonitrile (PAN) is among the most common polymer materials in the world thanks to its versatility in a wide range of applications. Of importance to this work is its use in electrochemical cells. PAN has seen use as a separator material and as a binder material in lithium-ion cells. Expanding upon innovations made in recent decades for electrodepositing PAN onto conductive surfaces, this work details methods used to apply PAN as a thin coating to graphite composite electrodes; the resultant films may then be used for further electrochemical analysis in a lithium-ion cell. Graphite electrodes coated with electrodeposited PAN films were produced of a practical size for electrochemical testing in Swagelok cells; optical microscopy images of the resulting PAN coated graphite electrodes were also recorded to study the morphology of the coating.